Computer-based self-help therapy: A qualitative analysis of attrition. (March 2019) - Hermes, Eric DA; Merrel, Jeremy; Clayton, Ashley; Morris, Christa; Rowe, Michael
The impact of computer-based cognitive-behavioral self-help therapy programs is limited by high attrition. This study explored reactions to computer-based cognitive-behavioral self-help therapy use among individuals not completing a full treatment course. Individuals receiving outpatient substance use disorder treatment at a Veterans Health Administration clinic who enrolled in a study implementing a computer-based cognitive-behavioral self-help therapy for insomnia, but subsequently dropped out prior to completion, were interviewed. Reactions to use and reasons for attrition were explored through thematic analysis of interviews. Among barriers to use, themes of competing demands, personal attributes, the computer-based format of computer-based cognitive-behavioral self-help therapies, and negative experiences with the specific program used were identified. Among facilitators of use, themes of personal support, the computer-based cognitive-behavioral self-help therapy format, and personal attributes were identified. Recommendations for future implementation efforts to include additional person-to-person contact during computer-based cognitive-behavioral self-help therapy participation were made. These themes may be employed to develop strategies for computer-based cognitive-behavioral self-help therapy implementation in order to maximize program engagement and completion.